The influence of parental awareness of the “Chinese double reduction” policy on junior high school students’ extracurricular physical exercise - Liu, Ping; Chen, Jin; Shen, Yangyang; Lou, Hu (Frontiers in Psychology, 2023)
Objective In this study, we aimed to explore the relationship between parental cognitive awareness (criticality, disruption and novelty cognition) of DBR, educational anxiety, and attitudes toward students’ physical exercise and students’ extracurricular physical exercise so as to construct and verify a conditional process model. Methods We adopted a stratified random cluster sampling approach and conducted a nationwide questionnaire survey with 2,700 junior high school students and their parents across 9 provinces, municipalities and autonomous regions. Results Parents generally had a certain degree of cognitive awareness of DBR. Criticality cognition and disruption cognition had a significant positive impact on junior high school students’ extracurricular physical exercise (β = 0.24, p < 0.01; β = 0.04, p < 0.05), but the effect of novelty cognition was not significant (β = −0.04, p = 0.06). Parents’ educational anxiety played a significant mediating role in parents’ cognition of DBR and students’ extracurricular physical exercise (criticality cognition: β = 0.10, 95% CI: 0.03–0.06; disruption cognition: β = 0.37, 95% CI: 0.31–0.42). Parents’ attitude toward students’ exercise also played a significant positive moderating effect in the mediation model (criticality cognition: β = 0.014, 95% CI: 0.002–0.031; disruption cognition: β = 0.010, 95% CI: 0.007–0.013). Conclusion Parents’ novelty, disruption, and criticality cognition of DBR have different effects on parents’ education anxiety and students’ extracurricular physical exercise, in which parental educational anxiety mediates the influence of DBR cognition on students’ extracurricular physical exercise, while attitudes toward students’ extracurricular physical exercise positively moderates the mediating effect.